Sexual and reproductive health factors associated with child, early and forced marriage and partnerships among refugee youth in a humanitarian setting in Uganda: Mixed methods findings - Loutet, Miranda G; Logie, Carmen H; Okumu, Moses; Berry, Isha; Lukone, Simon O; Kisubi, Nelson; Mcalpine, Alyssa; Mwima, Simon; Kyambadde, Peter (African journal of reproductive health, 2023)
Preventing early and forced marriage is a global priority, however, sexual and reproductive health (SRH) among youth remains understudied in humanitarian settings. This study examined child, early and forced marriage and partnership (CEFMP) among young refugees in Bidi Bidi refugee settlement, Uganda, and associations with SRH outcomes among young women. This mixed-methods study involved a qualitative phase with young (16-24 years) sexual violence survivors (n=58), elders (n=8) and healthcare providers (n=10), followed by a quantitative phase among refugee youth (16-24 years; n=120) during which sociodemographic and SRH data were collected. We examined SRH outcome differences by CEFMP using Fisher's exact test. Qualitative data showed that CEFMP was a significant problem facing refugee young women driven by stigma, gender norms and poverty. Among youth refugee survey participants, nearly one-third (31.7%) experienced CEFMP (57.9% women, 42.1% men). Among women in CEFMP compared to those who were not, a significantly higher proportion reported forced pregnancy (50.0% vs. 18.4%, p-value=0.018), forced abortion (45.4% vs. 7.0%, p-value=0.002), and missed school due to sexual violence (94.7% vs. 63.0%, p-value=0.016). This study illustrates the need for innovative community-engaged interventions to end CEFMP in humanitarian contexts in order to achieve sexual and reproductive health and rights for youth. (Afr J Reprod Health 2022; 26[12s]: 66-77).